1996
DOI: 10.1002/clc.4960190315
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of head‐up tilt test in patients with syncope

Abstract: Summary: As the head-up tilt test (HUT) is employed to verify the efficacy of undertalung a treatment, we prospectively evaluated the reproducibility of positive and negative results, as well as that of the response type in 64 consecutive patients (mean age 34.6 & 22.9 years) with syncope of unknown cause. Two HUTS (60 min, 75"), separated by an interval of 9.77 k 8.21 days, were performed on each patient. Positive responses were reproduced in the second HUT in 54.5% of the patients. A greater reproducibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Raviele et al 37 showed reproducibility to be 71% when the second examination is performed in an average of three 3 days after the first test. Blanc et al 38 , on the other hand, reported reproducibility to be 62% when the subsequent examination was undertaken after 7 days, but Ruiz et al 39 demonstrated that a positive TTT response could be reproduced in only 54.5% of the patients after a mean interval of 9.7 days (range 1 to 35 days). When the examinations were performed at average 7-day intervals, Hachul et al 40 observed the reproducibility of a positive response to be 82%, reduced to 77.8% when the same type of hemodynamic response was concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Raviele et al 37 showed reproducibility to be 71% when the second examination is performed in an average of three 3 days after the first test. Blanc et al 38 , on the other hand, reported reproducibility to be 62% when the subsequent examination was undertaken after 7 days, but Ruiz et al 39 demonstrated that a positive TTT response could be reproduced in only 54.5% of the patients after a mean interval of 9.7 days (range 1 to 35 days). When the examinations were performed at average 7-day intervals, Hachul et al 40 observed the reproducibility of a positive response to be 82%, reduced to 77.8% when the same type of hemodynamic response was concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the reproducibility of a positive TT varies broadly. Foglia-Manzillo et al [20 ]could reproduce a first positive TT in 77% of 34 patients, whereas Ruiz et al [21] found reproducibility rates for positive and negative TT results of 54.5 and 84.3%, respectively. For that reason, the TT is not a useful method to test therapeutic strategies for patients with vasovagal syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the reproducibility of a positive head-up tilt table test varies enormously. Foglia-Manzillo et al [37] could reproduce a first positive head-up tilt table test in 77% of 34 patients, whereas Ruiz et al [38] found a reproducibility rate for the positive and negative head-up tilt …”
Section: Special Tests In Suspected Vasovagal Syncope Tilt Table Testmentioning
confidence: 96%